(3QjGVI GdeYGbjfs - (3GdOdjej(B, (3fGgOI YHO RjOs ((3YeGfs (3OGQ UaGA ddfTQ hGdJhRjYs, 2022)
(3JYQjaGJ GdEYGbI , JYQjaGJ GdaQO GdeYGb, JUfja GdEYGbI, CfhGY GdEYGbI, GdEYGbI GdYbdjI, GdEYGbI GdSeYjI, GdEYGbI GdHUQjI, CfhGY GdEYGbI GdHUQjI, WQGFb GdhbGjI ef GdEYGbI GdHUQjI, GdEYGbI GdMQcjI, GdBKGQ GdfaSjI ddEYGbI, GdSeGJ GdTNUjI ddCaQGO GdeYGbjf, OhQ GdeLJeY aj QYGjI GdCaQGO GdeYGbjf, CSS GdJYGed eY GdCaQGO GdeYGbjf, QjGVI GdeYGbjf, fTCI QjGVI GdeYGbjf, JWhQ QjGVI GdeYGbjf MJi CfgG CUHMJ GhdeHjI, GdeSGHbGJ GdOhdjI, CgejI QjGVI GdeYGbjf, CgOGa QjGVI GdeYGbjf hCgejJgG, CfhGY QjGVI GdeYGbjf, GdGYJHGQGJ GdJj dG HO ef eQGYGJgG YfO GdefgL GdQjGVj ddeYGbjf, GdBKGQ GdEjLGHjI deeGQSI GdaQO GdeYGb ddCfTWI GdQjGVjI, JYQjaGJ GdJQHjI GdQjGVjI GdeYOdI, CSSgG, CgOGagG, hCSGdjHgG, GdCdYGH GdQjGVjI GdaQOjI hGdLeGYjI ddeYGbjf, GdCdYGH GdQjGVjI GdaQOjI cdYHI JfS GdWGhdI, aYGdjI GdSHGMI, aYGdjI QaY GdCKbGd, aYGdjI GdbhS hGdSge, aYGdjI GdeHGQRI Ydi GdcQGSj GdeJMQcI, aYGdjGJ CdYGH Gdbhi, SHGbGJ GdeVeGQ, GdCdYGH GdQjGVjI GdLeGYjIeKd dYHI GdcQI GdWGFQI ef GdLdhS, dYHI cQI GdSdI Ydi GdcQGSj GdeJMQcI,GdegGQGJ GdCSGSjI HcQI GdSdI Ydi GdcQGSj GdeJMQcI, cQI GdbOe GdHGQG ChdeHjI, dYHI cQI GdgOa, GdegGQGJ GdCSGSjI aj cQI GdgOa(B.s
Keywords: (3GdJQHjI GdHOfjIs; (3GdeYhbhfs